A complement to period/frequency estimation of a nonlinear oscillator. Issue 3 (December 2019) - He, Chun-Hui; Wang, Jian-Hong; Yao, Shao-wen
A fast estimation of periodic properties of a nonlinear oscillator is much needed as pointed out by Tian and Liu in their review article (Tian D and Liu Z, Journal of Low Frequency Noise, Vibration & Active Control, https://doi.org/10.1177/1461348418756013 ). Although a relatively high accuracy can be achieved, there is no way to continue the solution process to obtain any accuracy of a solution. This paper suggests an effective modification so that any accurate frequency can be obtained.